2013
DOI: 10.4085/1062-6050-48.1.16
|View full text |Cite
|
Sign up to set email alerts
|

National Athletic Trainers' Association Position Statement: Evaluation of Dietary Supplements for Performance Nutrition

Abstract: Objectives To help athletic trainers promote a “food-first” philosophy to support health and performance, understand federal and sport governing body rules and regulations regarding dietary supplements and banned substances, and become familiar with reliable resources for evaluating the safety, purity, and efficacy of dietary supplements. Background The dietary supplement industry is poorly regulated and takes in billions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
0
32
1
Order By: Relevance
“…The present study revealed that 8% of university students used AASs and that this was higher when compared to previous studies, which have reported AASs use as low as 1.1% [7]. The prevalence of AASs use in different populations of varying nationalities or countries has become a prominent research area in an attempt to determine the cause for the use of such AASs.…”
Section: Discussioncontrasting
confidence: 39%
“…The present study revealed that 8% of university students used AASs and that this was higher when compared to previous studies, which have reported AASs use as low as 1.1% [7]. The prevalence of AASs use in different populations of varying nationalities or countries has become a prominent research area in an attempt to determine the cause for the use of such AASs.…”
Section: Discussioncontrasting
confidence: 39%
“…The observed improvements were consistent with reported observations of improved RT in healthy individuals after caffeine ingestion, with doses ranging from 60 mg (a typical cup of coffee) to 250 mg. [5][6][7] Unfortunately, the dose of caffeine in my study was unknown because supplement manufacturers are not required to disclose this information on the product labels. 23 The same is true for the DMAA dose, as the ingredients were listed only as a proprietary blend. Not all researchers have reported RT improvements after caffeine ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that those considering supplementation first establish a sound dietary foundation, ensuring a balance in the foods consumed as well as maintaining constant hydration [62]. Furthermore, supplementation will be insignificant in producing desired results without an appropriate training stimulus (e.g.…”
Section: Resultsmentioning
confidence: 99%